Program Literasi Efektif Untuk Anak Madrasah Ibtidaiyah - Rusydiyah, Evi Fatimatur (Journal Of Islamic Elementary School (JIES), 2016)
Literacy can be defined technological literacy, information literacy, critical thinking, sensitive to the environment, even sensitive to politics. The process of literacy should start from childhood and family environment, supported in schools, socialized in the milieu, and the work environment. Therefore, it is vital that this program was implemented early on, in this case of primary education, especially students of Islamic Elementary School (MI) / Elementary School (SD). The idea of ??literacy programs are effective for children MI termed 5T + 1A, namely: (1) Time (the time is right, when, and for how long) learning literacy is given, (2) Task (tasks according to the needs, interests, backgrounds, and age of the student, (3) text (text selection), (4) teaching strategy (strategies used in teaching literacy effective, (5) Talk (learning skills oral language), and (6) assessment (type of assessment in accordance with needs, interests, backgrounds, and age of the student).